Risk factors for urolithiasis in patients with Crohn's disease. (15th November 2020) - Miyajima, Shigero; Ishii, Tatsu; Watanabe, Masato; Ueki, Toshiharu; Tanaka, Masatoshi
Abstract : Objective: To study the risk factors for urolithiasis in patients with Crohn's disease. Methods: This retrospective study included 1071 patients with Crohn's disease who were treated at a single center. Data pertaining to the following variables were analyzed: sex; age; type of Crohn's disease; number of intestinal resections; residual small intestine length; ileostomy; history of glucocorticoid therapy; and duration of Crohn's disease treatment. Results: Of the 1071 patients, 34 (28 male and six female) had urolithiasis (urolithiasis group) and 1037 (711 male and 326 female) did not (non‐urolithiasis group). The median residual small intestine length measured in the urolithiasis group (280.0 cm) was significantly shorter than that in the non‐urolithiasis group (342.5 cm; P  < 0.01). Significantly more patients in the urolithiasis group (14/34) received steroid medication than those in the non‐urolithiasis group (213/1037; P  < 0.01). On multivariate analysis, male sex (odds ratio 3.15; P  < 0.05), history of glucocorticoid therapy (odds ratio 3.07; P  < 0.05), and shorter residual small intestine length (odds ratio 0.99; P  < 0.01) were risk factors for the development of urolithiasis in patients with Crohn's disease. Conclusion: Our results suggest that male sex, history of glucocorticoid therapy, and shorter residual small intestine length are risk factors for urolithiasis in patients with Crohn's disease.